GPR39 promotes cardiac hypertrophy by regulating the AMPK–mTOR pathway and protein synthesis. (1st March 2021) - Liao, Hongjuan; Gao, Weinian; Ma, Jie; Xue, Hongyuan; Wang, Yi; Huang, Dai; Yan, Fang; Ye, Yuquan
Abstract: Hypertrophic growth of the cardiomyocytes is one of the core mechanisms underlying cardiac hypertrophy. However, the mechanism underlying cardiac hypertrophy remains not fully understood. Here we provided evidence that G protein‐coupled receptor 39 (GPR39) promotes cardiac hypertrophy via inhibiting AMP‐activated protein kinase (AMPK) signaling. GRP39 expression is overexpressed in hypertrophic hearts of humans and transverse aortic constriction (TAC)‐induced cardiac hypertrophy in mice. In neonatal cardiomyocytes, adenovirus‐mediated overexpression of GPR39 promoted angiotensin II‐induced cardiac hypertrophy, while GPR39 knockdown repressed hypertrophic response. Adeno‐associated virus 9‐mediated knockdown of GPR39 suppressed TAC‐induced decline in fraction shortening and ejection fraction, increase in heart weight and cardiomyocyte size, as well as overexpression of hypertrophic fetal genes. A mechanism study demonstrated that GPR39 repressed the activation of AMPK to activate the mammalian target of rapamycin (mTOR) and ribosomal protein S6 kinase β‐1 (S6K1), subsequently promoted de novo protein synthesis. Inhibition of mTOR with rapamycin blocked the effects of GPR39 overexpression on protein synthesis and repressed cardiac hypertrophy. Collectively, our findings demonstrated that GPR39 promoted cardiac hypertrophy via regulating the AMPK–mTOR–S6K1 signaling pathway, and GRP39 can be targeted for the treatment of cardiac hypertrophy.